Предмет: Алгебра,
автор: frgydrtu
найдите значение выражения -28ab-2(a-7b)^2 при a=корень из 13, b=корень из 3.
Приложения:
Ответы
Автор ответа:
0
-28ab - 2(a-7b)^2 = -28ab - 2(a^2 - 14ab +49b^2) = -28ab - 2a^2 +28ab - 98b^2 = -2a^2 - 98b^2 = -2*13 - 98*3 = -26 - 294 = -320
Автор ответа:
0
[tex]-28ab-2(a-7b)^2=-28ab-2(a^2-14ab+49b^2)=
\ =-28ab-2a^2+28ab-98b^2= \ =-2a^2-98b^2=-2(a^2+49b^2)
\ -2(13+49*3)=-2*160=-320
Похожие вопросы
Предмет: История,
автор: huaweiy62019
Предмет: Математика,
автор: mskovalhuk1977
Предмет: Физика,
автор: nurdostoktar
Предмет: Алгебра,
автор: оксаночка0301
Предмет: Математика,
автор: alvinamamedova